Comprehensive Genetic Analysis of Edible-Podded Pea Genotypes: Variability, Heritability, and Multivariate Approach Across Two Agro-Climatic Zones in India - Saurabh Yadav; Rajinder Kumar Dhall; Hira Singh; Parteek Kumar; Priti Sharma; Pradeep Kumar; Priyanka Kumari; Neha Rana (Horticulturae)
Evaluating genetically superior genotypes is essential for developing new hybrid varieties. This study aimed to assess the genetic diversity of 28 edible-podded pea genotypes by analyzing phenological traits, vigor, yield, and biochemical traits across two distinct agro-climatic zones in India. Significant variation was observed for most traits, with high genotypic and phenotypic coefficients of variation, heritability, and genetic advance, especially in vigor, yield, and biochemical traits. Phenological traits, except for the node at which the first flower appeared, exhibited minimal variability, indicating a high degree of uniformity. Yield per plant was negatively correlated with plant height but positively correlated with pod length, the number of seeds per pod, the number of pods per plant, and pod weight, indicating the potential for the simultaneous selection of these traits in breeding programs. Principal component analysis (PCA) identified six components explaining over 75% of the total variation, with yield and biochemical traits contributing the most to the observed diversity. These findings provide crucial insights for breeders aiming to improve quantitative traits, supporting the development of high-yielding and climate-resilient edible-podded pea varieties in India.